Soil Acidity Components Under Major Land Uses in Golaghat District of Assam - R.M. Karmakar; Samiron Dutta, Pallabi Kalita, Marami Dutta (Journal of the Indian Society of Soil Science, 2021)
Five representative soil profiles collected from five major land uses viz., forest cover (P1), rice cultivation (P2), tea plantation (P3), bamboo plantation (P4) and vegetable cultivation (P5) of Golaghat district of Assam were studied for soil acidity components in relation to land uses and physical and chemical properties of soils. The pH of the soils was in acidic range in all the pedons and DpH (pHKCl - pHw) was negative in all cases. Exchangeable Ca2+ was the dominant cation followed by exchangeable Mg2+, Na+ and K+. The exchangeable acidity was mostly constituted by exchangeable Al3+. Among all the forms of acidity, pH dependent acidity contributed significantly (more than 90%) towards total potential acidity in all the pedons which indicated the extent of variable charge present in the soils. Profile weighted mean of forms of acidity under various land uses depicted that the soils under rice cultivation (P2) exhibited maximum extractable, non-exchangeable and hydrolytic acidity, tea plantation (P3) exhibited maximum total acidity, exchangeable H+, exchangeable Al3+ and exchange acidity and bamboo plantation (P4) exhibited maximum pH dependent and total potential acidity. It was observed that the soils under forest cover (P1) and vegetable cultivation (P5) exhibited lower acidity compared to soils under other land uses in the present study. Various forms of soil acidity were significantly correlated with pHw, pHKCl, organic carbon, CEC, clay and exchangeable Ca2+.